Layout Planning For Production Facilities Using Line Balancing and ARC (Activity Relation Chart) Methods at UD. Agung Mulya - Hendri Setiawan; Atikha Sidhi Cahyana (Procedia of Engineering and Life Science, 2021)
Agung Mulya has experienced a decline in the production process, because there is an inefficient machine arrangement that causes delays in producing products, products with a target in a day can produce about 300 pcs of requests, can only produce about 170 pcs of requests, it is suspected that the main cause is the layout of the machine. less precise. In an effort to solve this problem, this study uses a method using Line Balancing and ARC (Activity Relation Chart) methods. This method is used for structuring the production flow so that there is a balance on all production lines so as to provide high efficiency on each production line. The balance in question is the balance of output from each stage of operation from the point of view of the production line and compiling a layout design for room facilities is used to analyze the proximity relationship using input data in the form of process flow, distance between spaces, conditions and spatial conditions From the results of this study resulted in a better re-lay out of thr production facility layout, the work station which originally had 8 workstations has decreased to 5 workstations, this is because the layout of the production flow layout can reduce the distance between work stations and the production process more efficient.